The Influence of Product Knowledge, Product Usability and Price toward Customer Preferences: (A Case of Samsung Smartphone Users in President University) - Suresh Kumar; Tiraz Aulia Aminin; Vania Vania; Opi Oktaviani (President University, 2016)
The growing smartphone industry makes consumers have more choices in determining which products they want to buy, so that the behavior and the reason in determining the choice will be very different from any individual or group. The aim of the research is to analyze the customer’s preference on Samsung smartphone by using the perspective of university. This research has 3 independent variables which are product knowledge, product usability, and price with dependent variable which is customer preferences. In this research, researcher used quantitative method and working through questionnaire distributed to 300 respondents consist of students, employees, and lecturers. Construct validity was checked through factor analysis and passed the convergent and discriminant validity. Reliability was checked through Cronbach’s alpha and passed (ranging from .688 to .842) , and then Structural Equation Modelling was applied as the method of hypothesis testing. Based on the result of the research, it shows that the most influence factor is product usability, and the second is price. For the product knowledge factor did not have any significant influence toward customer preference of smartphone. It is recommended that Samsung focus more on price and the benefits for its consumers. For future research, it is expected to expand the research to other big cities in Indonesia.